Vestibular Modulation of Long-Term Potentiation and NMDA Receptor Expression in the Hippocampus - Smith, Paul F.; Truchet, Bruno; Chaillan, Franck A.; Zheng, Yiwen; Besnard, Stephane (Frontiers in Molecular Neuroscience, 2020)
Loss of vestibular function is known to cause spatial memory deficits and hippocampal dysfunction, in terms of impaired place cell firing and abnormal theta rhythm. Based on these results, it has been of interest to determine whether vestibular loss also affects the development and maintenance of long-term potentiation (LTP) in the hippocampus. This paper summarizes and critically reviews the studies of hippocampal LTP following vestibular loss and its relationship to NMDA receptor expression, that have published to date. Although the available in vitro studies indicate that unilateral vestibular loss (UVL) results in reduced hippocampal field potentials in CA1 and the dentate gyrus, the in vivo studies involving bilateral vestibular loss (BVL) do not. This may be due to the differences between UVL and BVL or it could be a result of in vitro/in vivo differences. One in vitro study reported a decrease in LTP in hippocampal slices following UVL; however, the two available in vivo studies have reported different results: either no effect or an increase in EPSP/Population Spike (ES) potentiation. It is possible that this discrepancy is due to the different high frequency stimulation paradigms used to induce LTP. The increased ES potentiation following BVL may be related to an increase in synaptic NMDA receptors, possibly increasing the flow of vestibular input coming into CA1, with a loss of selectivity. This might cause increased excitability and synaptic noise, which might lead to a degradation of spatial learning and memory.